Effectiveness of Laptop Assisted Teaching about Cervical Cancer on Knowledge and Screening Behaviour Among Women in the Selected Rural Areas - Soniya. P, Soniya. P; Rajalakshmi, Rajalakshmi (Journal of Neonatal Surgery, 2025)
Cervical cancer remains one of the leading causes of cancer-related deaths among women in low-resource settings, primarily due to lack of awareness and inadequate screening. This study aimed to evaluate the effectiveness of laptop-assisted teaching in improving knowledge and screening behaviour regarding cervical cancer among women in selected rural areas of Puducherry. Methods: A randomized controlled trial was conducted among 60 women aged 35–55 years from the rural villages of Periakalapet and Pillaichavady. Participants were randomly assigned to an experimental group (n=30) and a control group (n=30). The intervention group received a structured laptop-assisted teaching session, while the control group received no intervention during the study period. Pre- and post-test assessments were conducted using a validated structured interview schedule measuring knowledge and screening behaviour. Data were analyzed using descriptive and inferential statistics, including paired and independent t-tests and chi-square tests. Results: Post-intervention, the experimental group showed a significant increase in mean knowledge scores (from 6.17 ± 2.74 to 17.60 ± 2.11; t = 21.617, p = 0.0005) and screening behaviour scores (from 10.03 ± 7.22 to 41.37 ± 5.10; t = 23.335, p = 0.0005). In contrast, the control group showed no significant improvement in knowledge (p = 0.778) or screening behaviour (p = 0.050). Moreover, 73.33% of women in the experimental group demonstrated adequate knowledge and 86.67% engaged in desirable screening practices post-intervention, compared to none at baseline. Conclusion: Laptop-assisted teaching was highly effective in improving both knowledge and screening behaviour related to cervical cancer among rural women.